Evaluation of Functional Recovery in Rats After Median Nerve Resection and Autograft Repair Using Computerized Gait Analysis - Heinzel, Johannes C.; Oberhauser, Viola; Keibl, Claudia; Swiadek, Nicole; Längle, Gregor; Frick, Helen; Kolbenschlag, Jonas; Prahm, Cosima; Grillari, Johannes; Hercher, David (Frontiers in Neuroscience, 2021)
Computerized gait analysis is a common evaluation method in rat models of hind limb nerve injuries, but its use remains unpublished in models of segmental nerve injury of the forelimb. It was the aim of this work to investigate if computerized gait analysis is a feasible evaluation method in a rat model of segmental median nerve injury and autograft repair. Ten male Lewis rats underwent resection of 7mm of the right median nerve with immediate autograft repair. The left median nerve was resected without repair and served as internal control. Animals were assessed for twelve weeks after surgery via CatWalk (CW) gait analysis every two weeks. Evaluation of motor recovery by means of the grasping test was performed weekly while electrophysiological measurements were performed at the end of the observation period. CW data was correlated with grasping strength at each postoperative time point. CW data was also correlated with electrophysiology using linear regression analysis. Principal component analysis was performed to identify clusters of outcome metrics. Recovery of motor function was observable four weeks after surgery, but grasping strength was significantly reduced (p<0.01) compared to baseline values until postoperative week 6. In terms of sensory recovery, the pain-related parameter Duty Cycle showed significant (p<0.05) recovery starting from postoperative week 8. The Print Area of the right paw was significantly (p<0.05) increased compared to the left side starting from postoperative week 10. Various parameters of gait correlated significantly (p<0.05) with mean and maximum grasping strength. However, only Stand Index showed a significant correlation with CMAP amplitude (p<0.05). With this work we prove that computerized gait analysis is a valid and feasible method to evaluate functional recovery after autograft repair of the rat median nerve. We were able to identify parameters such as Print Area, Duty Cycle and Stand Index which allow assessment of nerve regeneration. The course of these parameters following nerve resection without repair was also assessed. Additionally, external paw rotation was identified as valid parameter to evaluate motor reinnervation. In summary, computerized gait analysis is a valuable additional tool to study nerve regeneration in rats with median nerve injury.